What Are (English) Lessons For?. Issue 1 (2nd January 2019) - Bomford, Kate
ABSTRACT: This article takes as its starting-point four moments that occurred in the course of a year of teaching A-level English Literature in an inner-London sixth-form college. It argues that these moments represented forms of learning and experience that were valuable, but that fell outside the prevailing version of what (English) lessons are for. It uses these moments to challenge the current prescriptive and reductive models of what learning looks like, focussing on the relationship between knowledge and interpretation (with specific reference to Shakespeare), on the social dimension of learning, and on the relationship between learning and time. It concludes that the best lessons are potentially open-ended, unpredictable and unrepeatable.